Dynamic Analysis of a Multistory Building Using Response Spectrum Method (University of Thi-Qar Journal for Engineering Sciences, 2025)
Designing and analyzing structures to mitigate the effects of earthquakes is considered important, especially in recent times when earthquakes have increased in many places. This research includes analyzing a structure consisting of a basement and (G+14) stories, which encompasses a plan area measuring 32.20 m * 30.70 m. The building comprises a basement level serving as a car garage and 15 residential stories within coordinates (34.19205N) (45.12537E). The response spectrum analysis method, a linear dynamic method, was used, and the ETABS 21 program was adopted to perform this task. The conditions for the analysis in this way were done according to the ASCE/SEI7-16 code. This method includes several steps, where, in the beginning, the response spectrum function is defined, the earthquake is defined in the direction of both X and Y, and the source of the mass is determined. The effect of the geometric nonlinearity is also considered, in addition to 30 mode shapes, to reach the mass participation ratio equal to 100%. In order to perform the mentioned steps, several important variables must be entered, which are the reduction factor (R=4), spectral acceleration in the short and long direction (Ss=0.8, sl=0.2), and the damping value (5%). The analysis results included calculating the period, the center of mass and rigidity, but the main objective of this research was to calculate the base shear, which amounted to 2077 tons, and the story drift of the structure, which amounted to 0.0479. This value is considered high, as it exceeded the permissible value specified by the ASCE/SEI7-16 code, and therefore, the structure is considered unsafe in the event of an earthquake.